Effects of pelletization on biomethane production from wheat straw - Singh, Prakash (Environmental technology, 2025)
The high lignin content and low bulk density of wheat straw pose challenges for biogas production. To overcome these hurdles, pretreatment and biomass pelletization have emerged as viable options. Thus, this research aims to reduce the recalcitrant nature of WS by employing various thermal pretreatment techniques and identifying the optimum parameters (temperature and time). To prepare pellets, a mixture comprising wheat straw (subjected to the best pretreatment) and cow manure pellets (WCP) at varying substrate and binder (Svs/Bvs) ratios ranging from 0.5 to 2.5 were used. Parameters such as density, water absorption, and drop shattering were evaluated to evaluate the physical characteristics of produced WCP. Additionally, the biomethane yield test of WCP (exhibiting the most favourable physical characteristics) was performed with various total solids (TS) concentrations from 4 to 12%. The WS demonstrated the highest sCOD solubilisation of 9066 mg/L when subjected to a hot air oven pretreatment (90 min at 110°C). The physical qualities of WCP were found to be dependent on the Svs/Bvs ratio (with the optimal ratio being 2.0). It was also observed that a TS content of 6% yielded the highest biomethane production (253.85 mL/g-VSconsumed). In summary, this study's conclusion waves the path of management of wheat straw and cow dung while simultaneously generating bioenergy